Formations of terror - Bell, Simon (CAMBRIDGE SCHOLARS PUB, 2017)
There are a host of books about fear but, as yet, there has been little attempt to methodically and systemically assess how fear emerges and is targeted. This highly readable yet rigorous book sets about the methodical assessment of fear as an emergent property. Working from the personal experience of fear as 'everyman', and then using examples and case studies, it explores the main principles which lie behind the manifestation of fear of all kinds. Using climate change as its specific point of focus, fear is seen to be a major force in problem assessment and analysis and, by accident or inten.